Use of anticoagulant or antiplatelet agents is not related to epistaxis in patients undergoing transnasal endoscopy - Kobayashi, Yoshiya; Komazawa, Yoshinori; Yuki, Mika; Ishitobi, Hitomi; Nagaoka, Makoto; Takahashi, Yoshiko; Nakashima, Sayaka; Shizuku, Toshihiro; Kinoshita, Yoshikazu (Endoscopy International Open, 2018)
Background and study aims Unsedated transnasal endoscopy (uTNE) has become accepted as a safe and tolerable method for upper gastrointestinal tact examinations. Epistaxis is 1 of the major complications of TNE, though its risk factors have not been elucidated. Generally, patients administered an anticoagulant or antiplatelet drug are considered to have an increased risk of epistaxis during TNE. Here, we investigated risk factors of epistaxis in patients undergoing uTNE, with focus on those who received antithrombotic agents.Patients and methods We enrolled 6860 patients (average age 55.6 ± 12.97 years; 3405 males, 3455 females) who underwent uTNE and received the same preparations for the procedure. Epistaxis was evaluated using endoscopic images obtained while withdrawing the scope through the nostril. We also noted current use of medications including anticoagulant or antiplatelet agents prior to the endoscopic examination. Results Epistaxis occurred in 3.6 % of the enrolled patients (245/6860), and that rate was significantly higher in younger patients (average age 49.31 ± 11.8 years for epistaxis group vs. 55.83 ± 13.0 years for no epistaxis group, P < 0.01) as well as females (4.78 % vs. 2.35 %, P < 0.01). The odds ratio for occurrence of epistaxis was 2.31 (95 %CI: 1.746 – 3.167) in the younger patients and 2.02 (95 % CI: 1.542 – 2.659) in females. In contrast, there was no significant difference for rate of epistaxis between patients with and without treatment with an antithrombotic agent (3.0 % vs. 3.6 %). Conclusions The rate of epistaxis was higher in younger and female patients. Importantly, that rate was not significantly increased in patients who were administered an antithrombotic agent.